(untitled) (Innovative professional education, 2022)
In order to identify the peculiarities of the educational sector, the situation in the labor market of Ukraine as of October 1, 2022, was analyzed. The signs that the demand for educators exceeds the supply were identified and specified. Those sectoral disparities, theelimination of which is the prerogative of the educational sector in terms of achieving qualification matching of unemployed and unfilled vacancies, are analyzed. The scale of necessity and directions of modernization of the educational sector are outlined.